Comparative Translation Analysis of Subtitle and Dubbing in “Raya and the Last Dragon” - Annisa Aulia; Raden Arief Nugroho (Journal of English Language Teaching and Linguistics, 2022)
The objectives of this study are (1) to classify the translation techniques used between subtitles and dubbing (2) to identify the quality of the accuracy instrument between subtitles and dubbing (3) to compare the quality of the accuracy instrument that is more accurate to use. The source data is a movie that is limited to the translated utterances that have different translations in subtitle and dubbing versions. This study used a qualitative method with the following steps; (1) Classifying the translation techniques of subtitle and dubbing data based on Molina and Albir’s (2002) classification. (2) Tabulating the comparison of translation techniques between subtitles and dubbing. (3) Identifying the translation quality of accuracy based on the theory of Nababan et al., (4) Drawing conclusions. As a result, both subtitle and dubbing mostly used the established equivalent technique. An established equivalent has a good effect on the quality of accuracy obtained. This technique makes it easier for the audience to understand because it prioritizes the prevalence and naturalness so that the message from SL is conveyed properly. The researcher discovered that dubbing translation is more accurate than subtitle translation. Some subtitle translations are still considered less accurate. The researchers concluded that subtitles are appropriate for adolescents or adults, particularly foreign language learners. Language learners can broaden their knowledge of the language by watching films with subtitles. Meanwhile, dubbing is more appropriate for younger audiences because the language used is typically simpler to comprehend and does not contain swear words or inappropriate words.